PENGARUH SIKAP, NORMA SUBJEKTIF, KONTROL PERILAKU YANG DIPERSEPSIKAN TERHADAP NIAT UNTUK MEMBELI APARTEMEN DI DKI JAKARTA - SHERLY PANGESTIKA; KLEMENS WEDANAJI PRASASTYO (Jurnal Bisnis dan Akuntansi, 2017)
The aim of this research is to know the effect of attitude, subjective norm, and perceived behavioral control toward intention to purchase apartment in DKI Jakarta. The population of this research is the whole residents who live in Jabodetabek. The samples of data in this research were chosen by using purposive sampling. 193 questionnaires were being distributed in DKI Jakarta, and only 119 questionnaires which could be used as the data. This research used descriptive statistics analysis for demography, multiple regression analysis to examine the hypotheses. The result of this research showed that attitude, subjective norm, and behavior control had significant positive effect toward intention. The three variable were examined together, and the result showed that they had significant effect toward intention.Keyword: theory planned